Iterative Operator-splitting Methods with Embedded Discretization Schemes - Geiser, Jürgen (Communications in Mathematics and Applications, 2012)
In this paper we describe a computation of iterative operator-splitting method, which are known as competitive splitting methods, see [11] and [10]. We derived a closed form, based on commutators for the iterative method. The time discretization schemes apply extrapolation schemes and Pade approximations to the exp-functions. Spatial discretization schemes considered Lax-Wendroff methods and are combined with the iterative schemes. The error analysis describe the approximation errors. Numerical examples of ordinary and partial differential equations support the fast computation ideas.